Psycho-physiological benefits of mountain landscape environment as stimulus for directed attention restoration and stress mitigation - Ojobo, Henry (2015)
The evolutionary perspective of human-nature synergy maintains that humans evolved in natural environments over a long period. Hence, humans are largely adapted to nature. Several studies evaluating encounters with nature have been supportive of its restorative and therapeutic effects. However, most of the studies carried out in real-site, natural environments have been largely done in forests and wilderness, while mountain environments have merely been mentioned as part of picture slides or video simulations. Additionally, very little research in the assessment of nature and human wellbeing relationships has adopted a synergetic approach of the mix of real-site and psycho-physiological mode of measurement. This study explores the mechanism and intricacies of the link between restorative environments, human response and psycho-physiological wellbeing in Obudu mountain landscape environment in Nigeria. Psychological and physiological experiences were explored using quantitative research method to elicit subjective and objective responses from individuals. A total of 200 adults were engaged in the psychological measures of preference and perception of the environment, while 38 adults participated in the physiological experimental measures. A tripartite data collection strategy was utilised: (1) psychological data were elicited through selfreport measures using questionnaires, (2) physiological data were gathered through pre-test and post-test measures of blood pressure, pulse rate and respiratory rate, and (2) physical measurements of the ambient environment conditions were carried out to acquire temperature and humidity data. The data were analysed using inferential and descriptive statistics and content analysis. The results revealed that preference and perceptual patterns were incongruent with evolutionary assertions suggesting that the tendency of human stress mitigation in nature is not shaped by innate or evolutionary factors. Experiential contact with the mountain landscape environment influenced individual’s ability to attain a relaxed state through the reduction of their diastolic blood pressure and pulse rate. It was found that tangible psychological and physiological effects can be obtained through short term contact with a multistimulus mountain landscape environment. The study concludes that contact with mountain landscape environment promotes spontaneous recovery from stress and restoration of directed attention. Policy makers, designers and developers within the context of creating buildings and cities would eventually refer to this evidence as it pertains to the potential of mountain landscape environments in mental wellbeing promotion.